Ghan-jeevamrit discs: Turning natural farming into rural income - Pandey, Manish; Das, Umakant (Indian Farming, 2026)
This article presents an easy and cost-effective method to prepare solid ghan-jeevamrit discs, offering a practical solution for farmers and rural households for effective utilisation of the cow dung and urine. They are prepared using cow dung, cow urine, jaggery, gram flour and handful of soil using simple tools. They address key limitations of liquid jeevamrit by providing a product that is easy to store, transport and apply throughout the year. The article describes preparation of discs, their usefulness and support to both natural farming and rural income generation. By transforming a traditional bio-input into a value-added product, ghan-jeevamrit discs can open new opportunities for sustainable farming and small-scale entrepreneurship.